Molecular Genetic Characterization of a Cluster in A. terreus for Biosynthesis of the Meroterpenoid Terretonin - Guo, Chun-Jun; Knox, Benjamin P; Chiang, Yi-Ming; Lo, Hsien-Chun; Sanchez, James F; Lee, Kuan-Han; Oakley, Berl R; Bruno, Kenneth S; Wang, Clay C. C (Organic letters, 2012)
Meroterpenoids are natural products produced from polyketide and terpenoid precursors. A gene targeting system for A. terreus NIH2624 was developed, and a gene cluster for terretonin biosynthesis was characterized. The intermediates and shunt products were isolated from the mutant strains, and a pathway for terretonin biosynthesis is proposed. Analysis of two meroterpenoid pathways corresponding to terretonin in A. terreus and austinol in A. nidulans reveals that they are closely related evolutionarily.